The low-cycle fatigue deformation mechanisms of two single crystal superalloys at room temperature and 600 °C. (October 2019) - Zhang, Yaoli; Wang, Xinguang; Li, Jinguo; Cheng, Yin; Yang, Yanhong; Meng, Jie; Liu, Jinlai; Liu, Jide; Zhou, Yizhou; Sun, Xiaofeng
Abstract: The LCF behaviors of two Ni-based single-crystal superalloys at room temperature and 600 °C have been studied. Superalloy with 3 wt% Ru-containing (3Ru alloy) had more excellent fatigue performances than that of non-Ru superalloy (0Ru alloy). Microstructures observed by transmission electron microscope showed that 0Ru alloy exhibited slip bands with orthogonal slip directions after the test. (1ī1) [011] and (1ī1) [0ī1] slip systems were activated in plastic deformation process. While (111) [0ī1] and (1ī1) [0ī1] slip systems of 3Ru alloy were along the single slip direction. Therefore, adding alloying element Ru to the superalloy promoted uniform deformation and prolonged fatigue life. Graphical abstract: Unlabelled Image